A method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid

By using yttrium acetylacetonate as a sintering aid and combined with plasma activation sintering technology, the problem of reducing thermal conductivity caused by oxygen impurities in aluminum nitride ceramic materials is solved, and the preparation of aluminum nitride ceramic materials with high density and high thermal conductivity is achieved.

CN116589286BActive Publication Date: 2025-04-15WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310654590.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-04-15
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The thermal conductivity of existing aluminum nitride ceramic materials is reduced due to the high content of oxygen impurities, and the sintering aid is difficult to disperse evenly, affecting density and thermal conductivity.

Method used

Yttria acetylacetonate (Y(acac)3) soluble in organic solvents was used as the sintering aid, and after mixed with aluminum nitride powder, aluminum nitride ceramic materials were prepared by plasma activation sintering technology. This method removes oxygen impurities through carbon thermal reduction reaction, and improves the density and thermal conductivity of the ceramic.

Benefits of technology

The high density and high thermal conductivity of aluminum nitride ceramic materials are achieved, the thermal conductivity is increased by 128% to 110W/(m·K), and the generated second phase is uniformly distributed, reducing phonon scattering and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004268129080000011
    Figure HDA0004268129080000011
  • Figure HDA0004268129080000012
    Figure HDA0004268129080000012
  • Figure HDA0004268129080000013
    Figure HDA0004268129080000013
Patent Text Reader

Abstract

The present invention discloses a method for preparing aluminum nitride ceramics by using yttrium acetylacetonate as a sintering aid. After yttrium acetylacetonate powder is mixed with an organic solvent and heated, a certain mass ratio of aluminum nitride powder is added, and then mixed and ball-milled to obtain a mixed powder; the obtained mixed powder is subjected to plasma activation sintering to obtain an aluminum nitride ceramic block material. The present invention develops a new use of yttrium acetylacetonate as an aluminum nitride sintering aid. Using yttrium acetylacetonate as a sintering aid to prepare aluminum nitride ceramics effectively solves the problem of reduced thermal conductivity due to high oxygen impurity content during sintering of aluminum nitride powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic packaging materials, and in particular to a preparation method of aluminum nitride ceramics and a product thereof. Background Art

[0002] With the advent of the 5G era, the Internet of Everything has become a reality. With the development of microelectronics technology, the heat energy caused by the power consumption of higher power components needs to be solved, and the substrate as an electrical insulating material needs to have higher thermal conductivity and excellent dielectric properties.

[0003] In this case, aluminum nitride (AlN) ceramics are considered to be an ideal material for the next generation of semiconductor heat sinks and electronic device packaging due to their good thermal conductivity, linear expansion coefficient close to that of silicon and gallium nitride, high volume resistivity, and low dielectric constant and dielectric loss. Compared with the previous generation of heat sinks (Al2O3, BeO), the aluminum nitride production process is non-toxic and has a higher thermal conductivity.

[0004] However, aluminum nitride is a covalent compound with a small atomic self-diffusion coefficient, and requires a temperature of more than 1900°C to sinter into a dense ceramic material. Due to improper production and storage, impurities such as aluminum oxide and aluminum hydroxide are present in aluminum nitride powder. This is because the affinity between Al and O atoms is high, which causes O to enter the aluminum nitride lattice to produce aluminum vacancies. Aluminum vacancies scatter phonons and reduce thermal conductivity. The current method to solve oxygen defects is to add an appropriate amount of sintering aid to achieve liquid phase sintering to increase the density of the matrix and capture lattice oxygen, thereby obtaining a higher thermal conductivity. The sintering aids in current technology are mainly rare earth element oxides and fluorides, rare earth nitrates, alkaline earth metal oxides and fluorides. The most commonly used sintering aid in scientific research and production is a composite sintering aid of Y2O3 and CaO.

[0005] These aluminum nitride ceramic sintering aids are generally introduced in the form of solid phase, which is difficult to be evenly dispersed in the aluminum nitride matrix. On the one hand, this affects the performance of the sintering aid. On the other hand, the second phase with low thermal conductivity produced by it will aggregate and scatter phonon propagation, resulting in reduced thermal conductivity; and these sintering aids cannot generate aluminum-free phases to reduce the aluminum vacancy concentration. To solve this problem, external carbon materials are usually used for redox reactions. However, the oxidation process of carbon materials is prone to generate gas, and pores remain in the sintered body, reducing its density and thermal conductivity. At the same time, crystalline carbon such as graphite or graphene has poor bonding with aluminum nitride grains, and the composite interface between the two will produce severe phonon scattering; the addition of carbon materials will also increase the conductivity of aluminum nitride ceramics, thereby affecting the insulation properties required by the packaging substrate material. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing aluminum nitride ceramics by using yttrium acetylacetonate (Y(acac)3) soluble in an organic solvent as a sintering aid, which effectively solves the problem of reduced thermal conductivity due to high oxygen impurity content during powder sintering.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] The application of yttrium acetylacetonate as a sintering aid for aluminum nitride is characterized in that yttrium acetylacetonate is used as a sintering aid for preparing aluminum nitride ceramics, and yttrium acetylacetonate powder is mixed with aluminum nitride powder and ball-milled, and then aluminum nitride ceramic materials are prepared by sintering. The sintering system is: pressure 20-80MPa, protective atmosphere, heating to 1500-1800℃ at a heating rate of 50-150℃ / min at room temperature, heat preservation for 3-10min, and then cooling with the furnace. Of course, using a lower sintering temperature, such as 1500-1600℃, and a shorter heat preservation time of 3-5min can save energy.

[0009] The method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid comprises the following steps:

[0010] 1) Weighing yttrium acetylacetonate powder and aluminum nitride powder according to a mass ratio of yttrium acetylacetonate to AlN of 1:(5-25);

[0011] 2) mixing the yttrium acetylacetonate powder weighed in step 1) with an organic solvent, heating the mixture, mixing the mixture with aluminum nitride powder, ball milling the mixture, and vacuum drying the mixture to obtain a mixed powder;

[0012] 3) The mixed powder obtained in step 2) is subjected to plasma activated sintering (PAS) to obtain an aluminum nitride ceramic bulk material.

[0013] According to the above scheme, the aluminum nitride ceramic block material can also be processed by grinding to form an aluminum nitride ceramic sheet. The grinding machine is a grinder, a polisher, a diamond cutting machine, etc.

[0014] According to the above scheme, the aluminum nitride ceramic block material obtained in step 3) can be further heat treated at a temperature of 1700-2200°C and a treatment time of 4-12 hours. The reason for the heat treatment is that since PAS is a sintering technology for rapid sintering and densification, its sintering time is short and the second phase product has no time to react further, so heat treatment is used to promote the reaction. Before and after the heat treatment, the second phase product is mainly transformed from the aluminum-rich phase YAG to the aluminum-poor phase and aluminum-free phase YAM / YN / Y2O3. The vacancy concentration of aluminum nitride after heat treatment is lower, so the thermal conductivity is improved.

[0015] According to the above scheme, the particle size of the aluminum nitride powder in step 1) is 0.1-1 μm; the melting point of the yttrium acetylacetonate powder is 138-140°C.

[0016] According to the above scheme, the purity of the aluminum nitride powder in step 1) is above 95%, and the purity of the yttrium acetylacetonate powder is above 99%.

[0017] According to the above scheme, in step 2), the mass ratio of the organic solvent to the yttrium acetylacetonate powder is (80-120):1.

[0018] According to the above scheme, the organic solvent in step 2) is one or a mixture of any proportion of isopropanol, propanol, ethanol, etc.; the heating temperature is 30-60°C.

[0019] According to the above scheme, in step 2), the ball milling speed is 100-300 r / min, and the ball milling time is 0.5-1 h.

[0020] According to the above scheme, in step 2), the vacuum drying temperature is 50-70° C., and the vacuum drying time is 8-12 h.

[0021] According to the above scheme, in step 3), the mixed powder is pre-pressed into a block before plasma activation sintering, the pre-pressing pressure is 20 to 40 MPa, and the pressing time is 5 to 10 minutes.

[0022] According to the above scheme, in step 3), the sintering process conditions are: axial pressure 20-60MPa, protective atmosphere, heating to 1500-1700°C at a heating rate of 80-100°C / min at room temperature, keeping warm for 3-5min, and then cooling with the furnace.

[0023] The aluminum nitride ceramic prepared by the above method provided by the present invention has a high density (more than 99%), an average grain size of 7±2μm, and a thermal conductivity of 100-110(W / (m·K). Yttrium acetylacetonate is used as a sintering aid, and the second phase generated by it is evenly distributed at the triple grain boundary, which has the least effect on the thermal conductivity. Taking Example 1 as an example, the thermal conductivity of the prepared aluminum nitride ceramic is 128% higher than that of pure AlN ceramic, and 52% higher than that of AlN ceramic with the addition of traditional yttrium oxide.

[0024] The present invention selects yttrium acetylacetonate as a sintering aid to prepare aluminum nitride ceramics. Yttrium acetylacetonate can be dissolved in an organic solvent when heated and then evenly dispersed in aluminum nitride powder, and the liquid phase generation temperature is low, which is conducive to reducing the sintering temperature; moreover, the residual carbon source decomposed by yttrium acetylacetonate can undergo a carbothermal reduction reaction with oxygen impurities at the sintering temperature, thereby removing oxygen impurities and solving the oxygen defect problem, thereby improving the thermal conductivity of the aluminum nitride ceramic substrate.

[0025] Compared with the prior art, the beneficial effects of the present invention are: 1. The yttrium acetylacetonate provided by the present invention has very little impurity content and a stable structure, and can be dissolved in an organic solvent within the range of 30 to 60° C., thereby solving the problem of uneven mixing and dispersion of sintering aids in aluminum nitride powder. 2. Since the sintering aid of the present invention is a yttrium-containing compound, its deoxidation effect is much higher than that of alkaline earth metal oxides and fluorides, and the generated second phase (Y-Al-O ternary compound is the second phase generated by the reaction of the sintering aid and oxygen impurities (mainly aluminum oxide), and its function is to fix the lattice and surface oxygen impurities at the grain boundary by generating ternary compounds) is stable and distributed at the three-fork grain boundary; the generated second phase is evenly dispersed in the aluminum nitride matrix, and organic carbon residues can be generated during the heating process, and further react with the Y-Al-O ternary compound generated by yttrium oxide, and finally obtain aluminum-free compounds (aluminum-free compounds refer to the second phases such as YN and yttrium oxide), which further converts the aluminum in the second phase into aluminum nitride, which can reduce the overall aluminum vacancy concentration; at the same time, the organic carbon residues generated by the thermal decomposition of yttrium acetylacetonate can further undergo carbon thermal reduction reaction with oxygen impurities to deoxidize. The present invention effectively solves the problem of reduced thermal conductivity due to high oxygen impurity content in the sintering of aluminum nitride powder through the above two methods.

[0026] In addition, the process steps of the present invention are simple. Aluminum nitride ceramic materials are prepared by low-speed ball milling, drying, spark plasma sintering, and low-temperature sintering. Subsequently, a simple grinding process is used to obtain aluminum nitride ceramic blocks or sheets, which are applied to the preparation of aluminum nitride ceramics and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM microscopic morphology of aluminum nitride powder of Examples 1, 2, and 3;

[0028] Figure 2 XRD diagram of aluminum nitride powder of Examples 1, 2 and 3;

[0029] Figure 3 The SEM microscopic morphology and particle size distribution diagram of the aluminum nitride ceramic prepared in Example 1;

[0030] Figure 4 The SEM microscopic morphology and particle size distribution diagram of the aluminum nitride ceramic prepared in Example 2;

[0031] Figure 5 XRD pattern of the aluminum nitride ceramic prepared in Example 3;

[0032] Figure 6The thermal conductivity curve of aluminum nitride ceramics prepared by adding 4-13wt.% yttrium acetylacetonate, as well as the thermal conductivity of aluminum nitride ceramics added with traditional yttrium oxide sintering aids and the thermal conductivity of aluminum nitride ceramics without sintering additives under the same sintering parameters. Among them, 4-13wt.% yttrium acetylacetonate is the mass percentage of yttrium acetylacetonate to the total mass of yttrium acetylacetonate and aluminum nitride.

[0033] Figure 7 In a) and b) are the XRD spectra of the aluminum nitride ceramics prepared in step 3) and step 4) of Example 2, respectively.

[0034] Figure 8 Backscattered electron scanning images of the cross-section polishing of the aluminum nitride ceramic sample prepared in Example 1, wherein a) the sintering aid is yttrium oxide, as a control; b) the sintering aid is yttrium acetylacetonate, i.e. Example 1. DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0036] In the following examples, the purity of the aluminum nitride powder used as the raw material is 95%, and the particle size is in the range of 0.1 to 1 μm; the purity of the yttrium acetylacetonate powder is 99%.

[0037] In the following examples, a precision diamond cutting machine is used to cut the sintered aluminum nitride ceramic into 10*10mm 2 The block is then polished with a confidential grinder to grind the carburized layer on the upper and lower surfaces, and finally an aluminum nitride ceramic block with a thickness of 1 to 2 mm is obtained. The thermal diffusion coefficient of the sample is first measured using an LFA457 laser thermal conductivity instrument (Netzsch, Germany), and then the specific heat capacity of the sample is measured using a C80 microcalorimeter from Setaram, France. The thermal conductivity of the measured material is calculated using the following formula: λ = αρC, where ɑ is the thermal diffusion coefficient, ρ is the relative density, and C is the specific heat capacity; the test temperature is 25°C.

[0038] Example 1

[0039] The method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid comprises the following specific steps:

[0040] 1) Weighing yttrium acetylacetonate powder and aluminum nitride powder according to a mass ratio of aluminum nitride powder to yttrium acetylacetonate powder of 9:1 (i.e., 10 wt.% yttrium acetylacetonate, which is the mass percentage of yttrium acetylacetonate to the total mass of yttrium acetylacetonate and aluminum nitride);

[0041] 2) dissolving the yttrium acetylacetonate powder weighed in step 1) in ethanol and heating to 30° C., wherein the mass ratio of the yttrium acetylacetonate powder to the ethanol is 1:100, and adding the obtained mixed solution and the aluminum nitride powder into a ball mill, using zirconium oxide balls as grinding balls, and the mass ratio of the solid powder (i.e., the sum of the mass of the aluminum nitride powder and the yttrium acetylacetonate powder): the grinding ball is 1:10, the ball mill speed is 250 r / min, the ball milling time is 30 min, and the slurry obtained after ball milling is placed in a vacuum oven, the vacuum oven temperature is 70° C., and the vacuum drying time is 12 h to obtain a mixed powder;

[0042] 3) Grind the mixed powder obtained in step 2) and add it into a graphite mold for pre-pressing at 40 MPa for 10 min, then put the mold into a plasma activated sintering furnace, pressurize it at 40 MPa, and use a nitrogen atmosphere. Sinter it from room temperature at a heating rate of 100 °C / min to 1700 °C for 5 min; then grind the block material obtained by sintering to remove the graphite paper layer and the carburized layer, and finally obtain an aluminum nitride ceramic block.

[0043] Figure 3 The SEM image and particle size distribution diagram of the aluminum nitride ceramic prepared in this embodiment show that its grain size D50 = 7.0 ± 2.1 μm, basically in the range of 4 to 11 μm, and no obvious second phase is distributed at the grain boundary; and the thermal conductivity coefficient (thermal conductivity) of the aluminum nitride ceramic is 91.22 W / (m·K); the cross-section polished backscattered electron scanning diagram of the sample is as follows Figure 8 As shown, the white highlighted part is the Y-containing second phase. It can be clearly seen that compared with the sintering aid yttrium oxide, the second phase generated by yttrium acetylacetonate is more evenly dispersed.

[0044] Example 2

[0045] A method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid, the specific steps are as follows:

[0046] 1) Weighing yttrium acetylacetonate powder and aluminum nitride powder according to a mass ratio of aluminum nitride powder to yttrium acetylacetonate powder of 9:1 (i.e., 10 wt.% yttrium acetylacetonate);

[0047] 2) dissolving the yttrium acetylacetonate powder weighed in step 1) in ethanol and heating to 30° C., wherein the mass ratio of the yttrium acetylacetonate powder to the ethanol is 1:100, and adding the obtained mixed solution and the aluminum nitride powder into a ball mill, using zirconium oxide balls as grinding balls, the solid powder: grinding balls = 1:10 (mass ratio), the ball mill speed is 250 r / min, the ball milling time is 1 h, and the slurry obtained after ball milling is placed in a vacuum oven, the vacuum oven temperature is 70° C., and the vacuum drying time is 12 h to obtain a mixed powder;

[0048] 3) Grinding the mixed powder obtained in step 2) and adding it to a graphite mold for pre-pressing at 40 MPa for 10 min, then placing the mold in a plasma activated sintering furnace, pressurizing it at 40 MPa, in a nitrogen atmosphere, heating it from room temperature to 1600-1700°C (three samples were made at 1600°C, 1650°C and 1700°C) at a heating rate of 100°C / min, and sintering it for 5 min; then grinding the block material obtained by sintering to remove the graphite paper layer and the carburized layer to obtain an aluminum nitride ceramic block;

[0049] 4) The aluminum nitride ceramic block obtained in step 3) is subjected to a heat treatment at 1800° C. for 4 hours to obtain a heat-treated aluminum nitride ceramic.

[0050] like Figure 7 As shown, before and after the heat treatment, the second phase product mainly transforms from aluminum-rich phase YAG to aluminum-poor phase and aluminum-free phase YAM / YN / Y2O3. The YAG phase exists before the heat treatment, but no longer exists after the heat treatment.

[0051] Figure 4 The SEM image and particle size distribution diagram of the aluminum nitride ceramic obtained in step 4) of this embodiment show that the grain size D50 is 8.3±2.1 μm, mainly in the range of 6 to 12 μm, without obvious second phase; and the thermal conductivity coefficient of the aluminum nitride ceramic is 116.2 W / (m·K).

[0052] Example 3

[0053] A method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid, the specific steps are as follows:

[0054] 1) Weighing yttrium acetylacetonate powder and aluminum nitride powder according to a mass ratio of aluminum nitride powder to yttrium acetylacetonate powder of 20:1;

[0055] 2) dissolving the yttrium acetylacetonate powder weighed in step 1) in ethanol and heating to 30° C., wherein the mass ratio of the yttrium acetylacetonate powder to the ethanol is 1:100, and adding the obtained mixed solution and the aluminum nitride powder into a ball mill, using zirconium oxide balls as grinding balls, the solid powder: grinding balls = 1:10, the ball mill speed is 250 r / min, the ball milling time is 1 h, and the slurry obtained after ball milling is placed in a vacuum oven, the vacuum oven temperature is 70° C., and the vacuum drying time is 12 h to obtain a mixed powder;

[0056] 3) Grind the mixed powder obtained in step 2) and add it into a graphite mold for pre-pressing at 40 MPa for 10 min. Then put the mold into a plasma activated sintering furnace, pressurize it at 40 MPa, and use a nitrogen atmosphere. Sinter it from room temperature at a heating rate of 80 ° C / min to 1700 ° C, and keep it at this temperature for 5 min. Then grind the block material obtained by sintering to remove the graphite paper layer and the carburized layer, and finally obtain an aluminum nitride ceramic block.

[0057] Figure 5 The XRD pattern of the aluminum nitride ceramic prepared in this embodiment shows that in addition to the aluminum nitride phase, there is also a trace amount of the second phase yttrium aluminum garnet (Y3Al5O 12 ) exists, and there are no obvious other impurity peaks; and the thermal conductivity coefficient of the aluminum nitride ceramic is 45.56 (W / (m·K).

[0058] Example 4

[0059] A method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid, the specific steps are as follows:

[0060] 1) Weigh yttrium acetylacetonate powder and aluminum nitride powder according to a mass fraction of yttrium acetylacetonate powder of 4 to 13 wt.% (take ten samples of 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, and 13 wt.%, that is, the mass ratios of yttrium acetylacetonate to aluminum nitride are approximately 1:24, 1:19, 1:15.7, 1:13.3, 1:11.5, 1:10.1, 1:9, 1:8.1, 1:7.3, and 1:6.7, respectively, within the range of 1:(6 to 24));

[0061] 2) dissolving the yttrium acetylacetonate powder weighed in step 1) in ethanol and heating to 30° C., wherein the mass ratio of the yttrium acetylacetonate powder to the ethanol is 1:100, and adding the obtained mixed solution and the aluminum nitride powder into a ball mill, using zirconium oxide balls as grinding balls, the solid powder: grinding balls = 1:10 (mass ratio), the ball mill speed is 250 r / min, the ball milling time is 1 h, and the slurry obtained after ball milling is placed in a vacuum oven, the vacuum oven temperature is 70° C., and the vacuum drying time is 12 h to obtain a mixed powder;

[0062] 3) Grind the mixed powder obtained in step 2) and add it into a graphite mold for pre-pressing at 40 MPa for 10 min, then put the mold into a plasma activated sintering furnace, pressurize it at 40 MPa, and use a nitrogen atmosphere. Sinter it from room temperature at a heating rate of 100 °C / min to 1700 °C for 5 min; then grind the block material obtained by sintering to remove the graphite paper layer and the carburized layer, and finally obtain an aluminum nitride ceramic block.

[0063] Figure 6 From the thermal conductivity data curves of the 10 aluminum nitride ceramic block samples prepared in this embodiment, it can be seen that: with the increase of the yttrium acetylacetonate content, the thermal conductivity gradually increases, and then gradually decreases after reaching the peak value. This is because yttrium acetylacetonate produces more second phases, and the second phase itself has extremely low thermal conductivity, so it will affect the thermal conductivity of the aluminum nitride ceramic matrix, resulting in a decrease in thermal conductivity.

[0064] Finally, the aluminum nitride ceramics prepared by the above method provided by the present invention have a high density (more than 99%), an average grain size of 7±2μm, and a thermal conductivity of 90-110(W / (m·K). Yttrium acetylacetonate is used as a sintering aid and is soluble in an organic solvent, so that the generated second phase is evenly distributed at the triple grain boundary, which has the least effect on the thermal conductivity. With the addition of yttrium acetylacetonate, the thermal conductivity of the aluminum nitride ceramic first increases and then decreases. The aluminum nitride ceramics prepared by the PAS sintering technology in Example 1 have a thermal conductivity that is 128% higher than that of pure AlN ceramics and 52% higher than that of AlN ceramics with the addition of traditional yttrium oxide. Using other sintering processes such as pressureless sintering or hot pressing sintering and corresponding sintering equipment, compared with the traditional yttrium oxide sintering agent, the thermal conductivity of the aluminum nitride ceramics prepared under parallel conditions with yttrium acetylacetonate as the aluminum nitride sintering aid can also be improved to a certain extent.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid, characterized in that: The steps include: 1) Weighing yttrium acetylacetonate powder and aluminum nitride powder according to a mass ratio of yttrium acetylacetonate to aluminum nitride of 1:(5-25); wherein the particle size of the aluminum nitride powder is 0.1-1 μm, the purity of the aluminum nitride powder is more than 95%, and the purity of the yttrium acetylacetonate powder is more than 99%; 2) mixing the yttrium acetylacetonate powder weighed in step 1) with an organic solvent in a mass ratio of 1:(80-120) and heating to 30-60° C., mixing with aluminum nitride powder and ball milling, and vacuum drying to obtain a mixed powder; 3) Pre-pressing the mixed powder obtained in step 2) into a block, the pre-pressing pressure is 20-40 MPa, the pressing time is 5-10 min, and then plasma activation sintering is performed, the sintering pressure is 20-80 MPa, and the temperature is increased to 1500-1800° C. at a heating rate of 50-150° C. / min at room temperature under a protective atmosphere, and the temperature is kept for 3-10 min, and then cooled with the furnace to obtain an aluminum nitride ceramic block material; the density of the aluminum nitride ceramic block material is more than 99%, and the second phase component is mainly Y3Al5O 12 , and the second phase is evenly distributed at the triple grain boundary, the average grain size in the microstructure is 5~9μm, and the thermal conductivity of the product is 100~110W / (m·K); 4) The aluminum nitride ceramic block material obtained in step 3 is subjected to heat treatment at a temperature of 1700-2200°C for a treatment time of 4-12 hours, and finally a heat-treated aluminum nitride ceramic is obtained; in the heat treatment step, the main component of the second phase is Y3Al5O 12 Transformed into aluminum-free phases YN and Y2O3 via YAlO3 and / or Y4Al2O9.

2. The method for preparing aluminum nitride ceramics using yttrium acetylacetonate as a sintering aid according to claim 1, characterized in that: In step 2), the organic solvent is one or a mixture of any proportion of isopropanol, propanol, and ethanol.

Citation Information

Patent Citations

  • Electrostatic chuck AlN ceramic for IC equipment and preparation method thereof

    CN111302806A

  • Process for the production of granulated aluminum nitride and its use

    DE3630303A1